A digitally enhanced home-based physical activity intervention for high-risk middle school youth during COVID-19. Issue 1 (27th November 2021) - Tripicchio, Gina L; Jones, Gareth J; Hart, Chantelle N; Hyun, Moonsup; DeSabato, Emily; Giddings, Amy; Ehrhardt, Amanda; Rosenberg, Emily
Abstract: COVID-19 significantly impacted physical activity among high-risk youth. Camp from Home, a digitally enhanced home-based intervention, was developed to address physical activity disparities among middle school youth during COVID-19. Camp from Home enrolled 62 youth in 54 families from five schools in Philadelphia during the summer of 2020. The 6-week intervention comprised of (1) three home deliveries of "activity kits" including exercise equipment and activity booklets, (2) asynchronous sport and exercise videos posted to a private YouTube channel, and (3) supportive text-messages from health coaches. YouTube analytics and self-report surveys completed by parents and youth at baseline and at the end of programming were used to assess engagement, acceptability, and preliminary efficacy. Youth participants were 12.4 (1.2) years, 38.7% female and 90.3% Black/African American. At follow-up, 41 parents (75.9%) and 34 youth (54.8%) completed measures. Youth self-reported increases in self-efficacy (Δ M (sd) = 0.4(1.0), p = .03) and physical activity (Δ M (sd) = 4.2(7.9), p = .004), despite suboptimal engagement in digital program components. Overall, participants highly rated the program. Activity kits and text-messages from health coaches were rated as most helpful. Most parents (95.1%) and youth (83.8%) expressed interested in participating again in the future. A 6-week digitally enhanced, home-based physical activity intervention was acceptable and feasible among parents and youth during the summer of 2020, with youth reporting improvements in self-efficacy and physical activity. Summer programs are critical for reducing disparities in physical activity and hold potential for addressing key barriers for high-risk youth even outside the context of COVID-19.